Mr volumetry of total ventricular volume and total brain volume in normal adult population in Kelantan - Muhammad Azmi, Nur Farahwahida (2014)

(untitled)
Background: This study documented the normal value of total ventricular volume in adult Malay Kelantan population, the normal ventricular brain ratio and the differences in between genders. Methodology: 58 healthy subjects aged 40years and above were included whom undergone MRI brain examinations in HUSM. Axial and sagittal T1-weighted images retrieved from PACS were analysed. The brain and ventricular outlines were delineated using OSIRIX software. The sum of the ventricular area multiplied by 0.7 were calculated as the total ventricular volume in each patient. The ventricular brain ratio obtained by dividing the total ventricular volume with the brain volume and multiplied by 100. The volumes of ventricle and brain were analyzed using paired t-test. Independent t-test was used to analyze ventricular of both male and female. P value of less than 0.05 (p<0.05) was taken as significant. Results were expressed as mean ±standard deviation (SD). Result: The mean total ventricular volume was 21.67cm3 (12.82), while that for male and female was 28.14cm3 (15.61) and 16.02cm3 (5.50) respectively. Mean total ventricular to brain ratio (in percentage) for all subjects was 1.71 (0.89). Mean VBR for male subjects was 2.09 (1.11) and 1.37 (0.44) for female. There was significant difference of the mean total ventricular volume and VBR between male and female subjects (p value <0.05). Conclusion: This study has obtained the normal mean value for the total ventricular volume and ventricular brain ratio in adult Kelantan population, which are statistically significant difference between difference genders.